Kompetensi Sumber Daya Manusia Bank Syariah Berdasarkan Prinsip-prinsip Syariah Islam (Studi Kasus Pada BNI Syariah Surakarta) - Muhammad Tho’in (ITB AAS INDONESIA Surakarta, 2016)
This study aims to determine how it should be the competence of human resources of Islamic banking is based on the principles of Islamic Shariah. This study uses a phenomenological approach oriented qualitative descriptive. The technique of collecting data using interviews, participant observation, and study. Human resource competencies Islamic banking is based on the principles of Islamic law, the ability to modify banking products, also understand the contracts sharia combined with the principles of Islamic law includes not burdensome, reduce the burden, the determination of the law periodically, pay attention to the benefit, as well as equality and justice. With the principles of Islamic sharia combined with the ability to modify banking products, also understand the syariah contracts, the target growth in market share of Islamic banks can be achieved in accordance with expectations.The results of this study are the competence of human resources at BNI Syariah Surakarta at the level of the manager is good, supported by higher education, training a lot, as well as experience. While at the employee level still needs a lot of attention, because the level of education there are still low, still a little training, and experience is not adequate. Keywords: Competence of Human Resources, Islamic Bank, Principles of Islamic Sharia